Diversity Of Macro fungi At The Sitinjau Lauik Hill Forest Area West Sumatera - zultsatunni'mah zultsatunni'mah; Dezi Handayani (Jurnal Serambi Biologi, 2022)
Macro fungi are large fungi, they can be seen with the naked eye. The Sitinjau Lauik Hill Forest area is a suitable habitat for the growth of macro fungi. Information about the diversity species of macro-fungi and their use for the community around The Sitinjau Lauik Hill Forest area is still very minimal. Therefore, a study was conducted with the aim of making an inventory of the types of macro fungi found in The Sitinjau Lauik Hill Forest area. The method used in this research is a direct survey in the field by exploring the forest area. Identification of fungi is done by adjusting morphological characteristics with reference books and related journals. Based on the research that has been done, the macro fungi found are Cookeina sulcipes., Genoderma sp., G. boninense., G. carnosum., G. lucidium., Pycnoporus sanguineus., Trametes sp., T. vesicolor., Microporus sp., M. afinis., Polyporus sp., P. arcularius., Grifola sp., Lycoperdon bisidium., Pleurotus pulmonarius., Auricularia polytricha., A. auricula-judae., Marasmius sp., Coltricia cinamomea., Lentinus sajor-cajor. This it can be concluded that the macro fungi found in the Hill Sitinjau Lauik Forest area amounted to 20 types of species fungi originating from 2 divisio, 5 ordo, 9 family and 12 genus.